2019
DOI: 10.4236/wjet.2019.71001
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Modeling of Fuel Rich and Fuel Lean Catalytic Combustion of the Stabilized Confined Turbulent Gaseous Diffusion Flames

Abstract: The Response Surface Methodology (RSM) has been applied to explore the thermal structure of the experimentally studied catalytic combustion of stabilized confined turbulent gaseous diffusion flames. The Pt/γAl 2 O 3 and Pd/γAl 2 O 3 disc burners were situated in the combustion domain and the experiments were performed under both fuel-rich and fuel-lean conditions at a modified equivalence (fuel/air) ratio (Ø) of 0.75 and 0.25 respectively. The thermal structure of these catalytic flames developed over the Pt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A suitable power transformation to the response data has been recognized using the Box-Cox method for normalizing the data or equalizing its variance. This method indicated that sqrt(T) of the mean experimental temperature T dependent variable is the best transformation, so it has been employed to represent the response Y in Equation ( 2) [56].…”
Section: ( ) (mentioning
confidence: 99%
See 1 more Smart Citation
“…A suitable power transformation to the response data has been recognized using the Box-Cox method for normalizing the data or equalizing its variance. This method indicated that sqrt(T) of the mean experimental temperature T dependent variable is the best transformation, so it has been employed to represent the response Y in Equation ( 2) [56].…”
Section: ( ) (mentioning
confidence: 99%
“…The neural network has been applied to predict the response temperature for these situations [74]. The maximum temperature response and its corresponding input variables have been obtained by in- The RSM the results of cases b & c have been reported previously in our study [56] and depicted in Table 2(a). As for case a; the values of the mean experimental temperature T dependent variable cited along with the corresponding x and r [9]…”
Section: Simulation and Optimizationmentioning
confidence: 99%